Role of c-Cbl Carboxyl Terminus in Serotonin 5-HT(2A) Receptor Recycling and Resensitization - Baldys, Aleksander (American Society for Biochemistry and Molecular Biology, 2011)
The 5-hydroxytryptamine 2A receptor (5-HT(2A)R) undergoes constitutive and agonist-dependent internalization. Despite many advances in our understanding of G protein-coupled receptor trafficking, the exact mechanism of endocytic sorting of G protein-coupled receptors remains obscure. Recently, we have reported a novel finding documenting a global role for the ubiquitin ligase c-Cbl in regulating vesicular sorting of epidermal growth factor receptor (Baldys, A., Göoz, M., Morinelli, T. A., Lee, M. H., Raymond, J. R., Jr., Luttrell, L. M., and Raymond, J. R., Sr. (2009) Biochemistry 48, 1462–1473). Thus, we tested the hypothesis that c-Cbl might play a role in 5-HT(2A)R recycling. In this study, we demonstrated an association of 5-HT(2A)R with c-Cbl. Furthermore, down-regulation of c-Cbl by RNA interference blocked efficient recycling of 5-HT(2A)R to the plasma membrane. Immunofluorescence microscopy revealed that 5-HT(2A) receptors were trapped in early endosome antigen 1- and Rab11-positive sorting endosomes in cells overexpressing c-Cbl mutants lacking carboxyl termini. This inhibitory effect was associated with a relative decrease in association of c-Cbl truncation proteins with the 5-HT(2A)R, compared with that observed for the full-length c-Cbl fusion protein. Consistent with the delayed recycling, 5-HT(2A)R resensitization was greatly attenuated in the presence of c-Cbl mutants lacking carboxyl termini, as detected by changes in the cytosolic calcium. Taken together, these studies have led to the discovery that the C-terminal region of c-Cbl plays a crucial role in the temporal and spatial control of 5-HT(2A)R recycling.